Исследования активных ядер галактик в Крымской астрофизической обсерватории - Pronik, V.I. (Известия Крымской астрофизической обсерватории, 2007)
The history of discovery of activity in galactic nuclei and the beginning of their regular spectral and photometric observations at the Crimean astrophysical observatory are briefly described. The main results of active galactic nuclei investigations obtained at the CrAO during the last ten years are given.